Strength Training — Why can`t I just run? - Glover, S. (1999)
Marathon preparation is a mix of endurance, speed, flexibility and strength. A marathoner`s routine naturally emphasizes endurance. But, nice legs and a big heart aren`t license to ignore the other training components. Well-rounded training contributes to injury resistance and removes a few more obstacles to performing to our potential. This web issue focuses on strength training. Will strength training make you a better runner? Maybe. There are two levels to address — health and performance. Performance Factors Enhanced by Strength Training Drawbacks of Weight Training Women , Strength Gain and Muscle Mass Strength Training Guidelines Norms: Muscular Endurance (Women) Leg Strength (Women) Leg Strength (Men) Upper Body Strength (Women) Upper Body Strength (Men) Modified Push-Up Norms (Women) Push-Up Norms (Men) Fitness Test